2017
DOI: 10.1159/000477963
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Management of Umbilical Artery Flow Abnormalities during Open Fetal Surgery

Abstract: Introduction: Umbilical artery (UA) Doppler ultrasound is used to assess uteroplacental insufficiency. Absent or reversed end diastolic flow (AREDF) in the UA is associated with increased perinatal mortality in fetuses with intrauterine growth restriction. We describe the incidence of UA Doppler abnormalities during open fetal surgery. Methods: We conducted a retrospective review of patients undergoing open in utero myelomeningocele (MMC) repair between 2008 and 2015. Intermittent UA Dopplers were performed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
(35 reference statements)
1
20
2
Order By: Relevance
“…For example, a letter to a journal editor describing maternal convulsions during general anaesthesia was excluded as a case report according to our criteria. In this circumstance, it appears that the patient was also part of the cohort of a study that was included, but it is possible that other rare events published as case reports have been missed. An international, prospective registry of fetal and fetoscopic surgery, such as the Eurofoetus and NAFTNet registries, would be the best way to accurately determine complication types and rates and avoid missing rare complications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a letter to a journal editor describing maternal convulsions during general anaesthesia was excluded as a case report according to our criteria. In this circumstance, it appears that the patient was also part of the cohort of a study that was included, but it is possible that other rare events published as case reports have been missed. An international, prospective registry of fetal and fetoscopic surgery, such as the Eurofoetus and NAFTNet registries, would be the best way to accurately determine complication types and rates and avoid missing rare complications.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides an interesting proposal for the quantitative and practical evaluation of fetal heart function. This may be added to other echocardiographic protocols already described and above all may increase the safety of the procedure when combined with traditional monitoring of intraoperative fetal cardiac frequency . It is clear that among other limitations, this study does not consider a high number of cases; this topic should certainly be studied in greater detail.…”
Section: Discussionmentioning
confidence: 98%
“…This may be added to other echocardiographic protocols already described and above all may increase the safety of the procedure when combined with traditional monitoring of intraoperative fetal cardiac frequency. 3,4,7,10,11 It is clear that among other limitations, this study does not consider a high number of cases; this topic should certainly be studied in greater detail. We also emphasize that it is often difficult to achieve adequate images within a limited window of time because the intraoperative echocardiogram should not hinder the surgery.…”
Section: Ta B L E 3 Paired Comparison Of Myocardial Performance Indexmentioning
confidence: 99%
“…In patients with an anterior placenta, hysterotomy is either fundal or posterior. Some authors have suggested the use of intermittent umbilical artery Doppler ultrasonography during open fetal surgery, but the short-term impact of absent/reversed end-diastolic flow on fetal well-being remains elusive [ 18 ].…”
Section: Ultrasound Monitoring During Fetal Surgerymentioning
confidence: 99%